Prevalence, Characteristics, and Clonal Distribution of Escherichia coli Carrying Mobilized Colistin Resistance Gene mcr-1.1 in Swine Farms and Their Differences According to Swine Production Stages - Lee, Soomin; An, Jae-Uk; Woo, JungHa; Song, Hyokeun; Yi, Saehah; Kim, Woo-Hyun; Lee, Ju-Hoon; Ryu, Sangryeol; Cho, Seongbeom (Frontiers in Microbiology, 2022)
Global spread of Escherichia coli strains carrying the mobilized colistin resistance gene mcr-1.1 (MCR1-EC) poses serious threats to public health. Colistin has been generally prescribed for swine colibacillosis, having made swine farms as major reservoirs of MCR1-EC. The present study aimed to understand characteristic differences of MCR1-EC, including prevalence, antimicrobial resistance, and virulence, according to swine production stages. In addition, genetic relatedness was evaluated between MCR1-EC isolated from this study as well as pig-, human-, and chicken-derived strains published in the National Center for Biotechnology Information (NCBI), based on the multi-locus sequence types (MLSTs) and whole-genome sequences (WGS). Individual fecal samples (n = 331) were collected from asymptomatic weaning-piglets, growers, finishers, and sows from 10 farrow-to-finishing farms in South Korea between 2017 and 2019. The weighted prevalence of MCR1-EC was 11.6% (95% CI: 8.9%–15.0%, 55/331), with the highest prevalence at weaning stage. The 96.2% of MCR1-EC showed multi-drug resistance. Notably, weaning stage-derived MCR1-EC showed higher resistance rates (e.g., against extended-spectrum β-lactams or quinolones) than those from other stages. MCR1-EC with virulence advantages (e.g., intestinal/extraintestinal pathogenic E. coli or robust biofilm formation) were identified from all pig stages, accounting for nearly half of the total strains. WGS-based in-depth characterization showed that intestinal pathogenic MCR1-EC harbored multi-drug resistance and multiple virulence factors, which were highly shared between strains isolated from pigs of different stages. The clonal distribution of MCR1-EC was shared within swine farms but rarely across farms. The major clonal type of MCR1-EC from swine farms and NCBI database was ST10-A. Core genomes of MCR1-EC isolated from individuals within closed environments (same farms or human hospitals) were highly shared (genetic distance < 0.01), suggesting a high probability of clonal expansion of MCR1-EC within closed environments such as livestock husbandry. To the best of our knowledge, this is the first study to analyze the differences in the characteristics and clonal distribution of MCR1-EC according to production stages in swine farms, an important reservoir of MCR1-EC. Our results highlight the need to establish MCR1-EC control plans in swine farms based on an in-depth understanding of MCR1-EC characteristics according to swine production stages, focusing especially on the weaning stages.